PENGARUH FAKTOR BAURAN PEMASARAN DALAM MEMPENGARUHI KEPUTUSAN KONSUMEN MEMBELI BERAS MEREK DUA BANDENG (Studi Pada UD. Iska Kecamatan Lape) - Desti Ademulianti; Alwan Wijaya; Marisha Sutanty (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of marketing mix factors including price, product, place and promotion either partially or simultaneously on the purchasing decision of Dua Bandeng brand rice at UD. Iska, Lape Sub-District. This type of research is associative research. The population in this study were all customers who purchased Dua Bandeng brand rice at UD. Iska, Lape Sub-District. The sampling technique used is incidental sampling, with this technique obtained 50 people as samples. The data collection method used is a questionnaire. Data analysis was carried out using multiple linear regression analysis techniques, t and F tests, and the coefficient of determination (R2) test. The results of this study indicate that the price, product, place and promotion have a positive and significant effect on purchasing decisions of Dua Bandeng brand rice at UD. Iska, Lape Sub-District, either partially or simultaneously. The degree of influence of price, product, place and promotion on purchasing decisions of Dua Bandeng brand rice at UD. Iska, Lape Sub-District is 76.6%, while the remaining 23.4% is influenced by other variables not examined. This shows that the better the price, product, place and promotion given, it will increase purchasing decisions of Dua Bandeng brand rice at UD. Iska, Lape Sub-District.